The good left undone : a novel - Trigiani, Adriana (Dutton, 2022)
"From present day Viareggio to Glasgow during World War II, a multigenerational sweeping tale of love lost, family secrets, and reconciliation over decades from New York Times bestselling author Adriana Trigiani"--
Keywords: Women -- Fiction; Family secrets -- Fiction; World War, 1939-1945 -- Fiction; Historical fiction